ANALYSIS OF CONSUMER ATTITUDE TOWARD BRAND EXTENSION OF PRENAGEN - Kressy Arba Yuniar; Lukman Hakim; Wakhid Slamet Ciptono (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Good brand will provide quality assurance for the company, because brand is not just a name but a brand is an asset of the company. Prenagen Junior, a brand extension of Prenagen products for pregnancy and lactation, is a fictitious experiment in this study. The aim of the research was to analyze consumer attitudes towards brand extension. The method used pre-experiment_one shot case study. The population was taken from respondents who had used  Prenagen products either Prenagen Esensis, Prenagen  Emesis,  Prenagen  Mommy,  or  Prenagen  Lactamom  within  last  6 months. A sample of 154 respondents was drawn from that population. The results obtained were analyzed using multiple regression analysis method. The results simultaneously showed that the similarity, brand reputation of origin, perceived risk, and innovativeness delivered a significant influence on consumers’ attitude towards brand extension (R2 : 0.556; p < 0.05).   The similarity of brand extension product with the parent brand, the parent brand’s reputation, perceived  risk  had  a  significant  influence  by  20.8  %,  10.0  %,  and  23.3  % respectively  on  the  consumers’  attitude  towards  the  brand  extension  product. While the innovativeness variable was not significant influence on that (B : 0.126 ; p > 0.05).Keywords:  Brand  Extension,  Similarity,  Reputation  Of  The  Parent  Brand, Perceived Risk, Innovativeness, Consumer Attitudes